SEMIOTICS ANALYSIS OF AHOK-DJAROT’S CAMPAIGN VIDEO ON YOUTUBE SOCIAL MEDIA FOR THE SECOND ROUND OF THE 2017 DKI JAKARTA GUBERNATORIAL ELECTION - Muhammad Alhada Fuadilah Habib; Asik Putri Ayusari Ratnaningsih; Michael Jeffri Sinabutar (Journal of Urban Sociology, 2021)
This study focuses on the messages conveyed in Ahok-Djarot’s campaign video on Youtube social media for the second round of the 2017 DKI Jakarta gubernatorial election by exploring and analyzing the elements of the icons, the indexes, the symbols, the lyrics, and the storyline using Peirce's semiotics based on the visual methodology. Various messages that have been conveyed through the video with the title “Video Kampanye Ahok-Djarot: Pastikan Pancasila Hadir di Jakarta” (Ahok-Djarot’s Campaign Video: Ensure Pancasila is Present in Jakarta) are very interesting to study because the video has become a viral video during the heating up political climate for the second round of the 2017 DKI Jakarta gubernatorial election. A form of support for Ahok-Djarot and also a form of criticism for the current condition of Jakarta articulated through a 2-minutes video with visual images as well as audio lyrics with subtitles packaged interestingly. The results obtained from the analysis are; when Ahok-Jarot’s campaign video for the second round of the 2017 DKI Jakarta gubernatorial election is mapped, it has three main scenes and each scene tries to convey a message to the public, especially the Jakarta citizens. The first scene shows that the current condition of Jakarta is still intolerant and tends to discriminate against minorities. The second scene tries to show that Jakarta should really hold the motto "Bhineka Tunggal Ika" (Unity in Diversity) and should not just use it as a mere motto. The third scene tries to show that Ahok-Jarot are the suitable leaders for the Jakarta citizens because Ahok has worked for Jakarta and has put real efforts for Jakarta. Moreover, Ahok-Djarot is a pair of candidates who can solve the problems described in the previous scene. In general, the issue raised in this controversial video is the issue of intolerance currently considered as a big problem for the Jakarta citizens.  Keywords: Semiotics, Intolerance, Political Campaign, Youtube Social Media, Ahok-Djarot, Jakarta